Effects of hysterectomy with simultaneous bilateral salpingectomy on the subsequent pelvic mass - Xiaopei Chao; Xiaoxia Wang; Yu Xiao; Mingliang Ji; Shu Wang; Honghui Shi; Qingbo Fan; Lan Zhu; Jinhua Leng; Dawei Sun; Jinghe Lang (BMC, 2019)
Abstract Objectives To analyze the clinicopathological characteristics of subsequent pelvic masses after hysterectomy for benign diseases, and to compare the masses following hysterectomy with or without simultaneous bilateral salpingectomy. Methods This study retrospectively analyzed patients undergone reoperation for pelvic mass subsequently to previous hysterectomy for benign disease from January 2012 to December 2016 in Peking Union Medical College Hospital. Results A total of 247 patients were enrolled in this study, of which 80.16% (n = 198) received simple hysterectomy, and 5.67% (n = 14) underwent hysterectomy with bilateral salpingectomy. The clinicopathological data of patients undergone simple hysterectomy or simultaneous bilateral salpingectomy was compared. In the former group, we found that 68.18% (n = 135) of the pelvic massed were benign, and the remaining 31.82% (n = 63) were malignant. In latter group, 57.10% (n = 8) were benign (8%) and 42.90% (n = 6) were malignant. Univariate analysis showed that the age of surgery for pelvic masses in patients undergoing hysterectomy with simultaneous bilateral salpingectomy was significantly younger than that in patients without salpingectomy (median, 44.5 vs 50 years, P < 0.0001), and the time interval between hysterectomy and onset of pelvic masses was also significantly shorter (median, 2 vs 5 years, P < 0.0001). And the probability of pelvic encapsulated effusion was significantly higher for the salpingectomy group. Multivariate analysis showed that there was no significant difference of the age of resection of pelvic mass, the time interval hysterectomy and pelvic mass onset, and the probability of pelvic encapsulated effusion between the two groups. Conclusions The results showed that the incidence of secondary benign pelvic masses may be reduced when hysterectomy was performed with simultaneous bilateral salpingectomy. However, there was no statistical difference in the clinical characteristics and pathological types of pelvic masses between patients received hysterectomy with or without salpingectomy.